2023
DOI: 10.1002/vetr.2591
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance of endometrial bacterial isolates collected from UK Thoroughbred mares between 2014 and 2020

Abstract: Background: Antimicrobial resistance (AMR) is important in equine reproduction, as antimicrobials have historically been widely used in the management of breeding mares. However, evidence of the characteristics of AMR in uterine isolates is limited in the UK. The objective of this retrospective study was therefore to describe temporal changes in AMR patterns of bacteria isolated from the endometrium of Thoroughbred broodmares in south-east England between 2014 and 2020. Method: Endometrial swabs were processed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…In summary, this study has, for the first time, estimated the population-level prevalence of isolates in over 18,000 endometrial-swab samples collected over a 7-year period from Thoroughbred broodmares in the UK, and has evaluated the variation in overall prevalence and the prevalence of the most common isolates according to year of sampling, mare age and cytology findings. These results provide much-needed population-level benchmarking of key bacterial species in a UK setting and compliment the findings from our larger body of work [ 18 , 19 ], which aims to highlight important limitations in current practices in terms of the use of unguarded endometrial swabs and the routine pre-breeding swabbing of clinically normal mares. Our findings also highlight knowledge gaps in the understanding of uterine “health” and “disease” in Thoroughbred broodmares and can inform future research to improve both antimicrobial stewardship and Thoroughbred reproductive health and productivity.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In summary, this study has, for the first time, estimated the population-level prevalence of isolates in over 18,000 endometrial-swab samples collected over a 7-year period from Thoroughbred broodmares in the UK, and has evaluated the variation in overall prevalence and the prevalence of the most common isolates according to year of sampling, mare age and cytology findings. These results provide much-needed population-level benchmarking of key bacterial species in a UK setting and compliment the findings from our larger body of work [ 18 , 19 ], which aims to highlight important limitations in current practices in terms of the use of unguarded endometrial swabs and the routine pre-breeding swabbing of clinically normal mares. Our findings also highlight knowledge gaps in the understanding of uterine “health” and “disease” in Thoroughbred broodmares and can inform future research to improve both antimicrobial stewardship and Thoroughbred reproductive health and productivity.…”
Section: Discussionsupporting
confidence: 78%
“…The overall prevalence of all types of isolates reported in the present study (35%) is in keeping with isolate frequencies reported from a study of 2311 uterine swab samples submitted to a laboratory in Ithaca, USA between 2007 and 2017 (39%) [ 17 ]. It is also similar to those from 8269 pre-breeding or diagnostic uterine samples from 7655 mares (swabs (95%), flushes or biopsies) submitted to a laboratory in Florida, USA between 2003 and 2008 (31%) [ 18 ], and from 394 routine pre-breeding samples (315 swabs, 79 flushes) submitted to a laboratory in Italy between 2014 and 2018 (33%) [ 19 ]. It is, however, much higher than frequencies reported from studies exclusively using guarded swabs for 2660 routine pre-breeding samples collected from 1621 mares on 17 Thoroughbred studs in Australia (7%) [ 10 ] and 2123 pre-breeding and diagnostic samples collected from 970 mares in the USA between 2001 and 2004 (11%) [ 11 ].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Antibiotic resistance of bacteria isolated from equine reproductive organs has been reported for animals with fertility problems, as shown in studies performed in various countries in Europe (France [ 10 , 130 ], Germany [ 136 ], Italy [ 42 , 137 ], Slovakia [ 43 ], Sweden [ 20 ], Turkey [ 138 ], United Kingdom [ 139 ]) and elsewhere (Brazil [ 140 ], Canada [ 141 ], India [ 142 ], United States of America [ 143 ]). Antimicrobials are commonly used to treat empirically reproductive disorders.…”
Section: Antibiotic Resistance As a Limiting Factor In Treatmentmentioning
confidence: 99%